Revolusi Integritas Pengusaha E-Commerce Indonesia di Era Society 5.0: Analisis QS. Hud: 84-85 - Khozinul Alim (At-Tahfidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2022)
E-commerce is one of the many forms of progress that emerged from the development of the internet. E-commerce offers convenience in shopping. This is one of the reasons why online shopping is preferred by most of the people. But this convenience makes some people take advantage of it for criminal acts. If this continues, e-commerce, which should lift the economy, will actually hamper the economy itself. To examine this reality in depth, in this study there are two big questions, namely first, how is the interpretation and contextualization of Q.S. Hud [11]: 84-85?. The second is how the implementation of the story of the Madyans in Q.S. Hud [11]: 84-85 on the revolution in the integrity of e-commerce entrepreneurs in Indonesia?. To explore and manage data comprehensively, in this study the researcher used the library study method. From this study the authors found: (1) In the case of buying and selling in e-commerce, Q.S. Hud [11]: 84-85 indicates that the purpose of buying and selling transactions is not only to gain profit, but is also expected to create social justice in buying and selling. This verse is an inspiration for a mental revolution to build integrity based on honest, polite, and responsible characters in the buying and selling business in e-commerce; (2) A structured system is needed to guard the actualization of the values ??????described by the Madyan people in Q.S. Hud [11]: 84-85. In addition, the mental revolution of e-commerce entrepreneurs in building integrity is important to do as an effort to ground the values ??????of the Qur'an in everyday life, by monitoring, standardizing and certifying e-commerce shops. If this effort is realized, in the era of society 5.0 this will help grow the wheels of the Indonesian economy through e-commerce efforts.